THE CHARACTERISTIC OF PATIENTS WITH FEMORAL FRACTURE IN DEPARTMENT OF ORTHOPAEDIC AND TRAUMATOLOGY RSUD DR. SOETOMO SURABAYA 2013 – 2016 - Riswanda Noorisa; Dwi Apriliwati; Abdul Aziz; Sulis Bayusentono (Journal Orthopaedi and Traumatology Surabaya, 2017)
Fracture is a neuromuscular damage due to tissue trauma or discontinue of bones. Fractures of the lower limbs due to accidents have the highest prevalence among other fractures in Indonesia. The aim of this study is to determine the characteristic of patients with femoral fracture in Department of Orthopedic RSUD Dr. Soetomo Surabaya.This research is retrospective observational. We analyzed medical records of all stay in patient in Department of Traumatic and Orthopedic RSUD Dr. Soetomo Surabaya during 1 January 2013 – 31 December 2016.  Of the 972 enumerated, 112 subjects with femoral fracture were analyzed for study. The observed variable of patients' profile include: sex, age, cause of fracture, type of wound, location of fracture, place of accident, time of accident.Our observational study during three years has concluded several findings as following. The most common cases of fracture is occurred at the age 15 – 24 with 40 cases (36%). Most of the cases is dominated by male gender (72%). Traffic accident (92%) is the major cause of fracture, which mostly occurred on the street (92%) at 06:01 A.M. until 12:00 A.M (28%). Closed wound (71%) is commonly found in femoral fracture. The most common type of femoral fracture has a closed wound (71%) and located in column of femur (46%). The most common cases of femoral fracture are occurred on male at the productive age due to traffic accident injury.